2018
DOI: 10.3389/fimmu.2018.03035
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific IgG Subclasses in Primary and Malignancy-Associated Membranous Nephropathy

Abstract: Membranous nephropathy (MN) is an autoimmune disease caused by binding of circulating antibodies to podocyte antigens in the kidney. For decades and still today primary MN has been considered to have an unspecified IgG4-driven autoimmune genesis, while secondary MN has been associated with other diseases, most notably cancer, and not linked to IgG4. Immunologic mechanisms of primary and malignancy-associated MN are assumed to be different, however, this has never been systematically evaluated. The identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 24 publications
1
58
0
1
Order By: Relevance
“…In addition, erlotinib demonstrated its renoprotective effects against renal fibrosis in 5/6 nephrectomized rats via inhibition of the Akt and ERK 1/2 signalling pathways associated with renal fibrosis . Despite these results, we think that the response of tumour to erlotinib is the major cause of MN remission, because of reports in the literature that the complete remission of MN occurred only in patients with tumour remission, whereas complete remission of MN did not occur in any of the patients whose tumours were not in remission …”
Section: Case Descriptionmentioning
confidence: 89%
See 4 more Smart Citations
“…In addition, erlotinib demonstrated its renoprotective effects against renal fibrosis in 5/6 nephrectomized rats via inhibition of the Akt and ERK 1/2 signalling pathways associated with renal fibrosis . Despite these results, we think that the response of tumour to erlotinib is the major cause of MN remission, because of reports in the literature that the complete remission of MN occurred only in patients with tumour remission, whereas complete remission of MN did not occur in any of the patients whose tumours were not in remission …”
Section: Case Descriptionmentioning
confidence: 89%
“…Recent studies have not found differences between the distributions of the IgG subclasses (PLA2R1 or THSD7A) in patients with primary vs. cancer‐associated MN, and no association with disease outcome . Both podocytes and lung bronchioles showed expression of PLA2R1 and thrombospondin type‐1 domain‐containing 7A (THSD7A) by immunofluoroscopy and Western blotting . Altogether, these findings indicate that antigen‐specific IgG subclasses do not allow differentiation between primary MN and malignancy‐associated MN nor prediction of disease outcomes.…”
Section: Case Descriptionmentioning
confidence: 92%
See 3 more Smart Citations